2019
DOI: 10.1021/acsomega.9b00304
|View full text |Cite
|
Sign up to set email alerts
|

Green Nanotechnology-Driven Drug Delivery Assemblies

Abstract: Green nanotechnology incorporates the principles of green chemistry and green engineering to fabricate innocuous and eco-friendly nanoassemblies to combat the problems affecting the human health or environment. Subsequently, amalgamation of green nanotechnology with drug delivery area has actually commenced a new realm of “green nanomedicine”. The burgeoning demand for green nanotechnology-driven drug delivery systems has led to the development of different types of delivery devices, like inorganic (metallic) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(48 citation statements)
references
References 108 publications
0
48
0
Order By: Relevance
“…PI is a stabilizing agent and reservoir for triiodide anions releasing free molecular iodine for biocidal action [32,48]. AgNP is a drug carrier and adsorbs TCA, Cinn, and PI on its large surface [57,60]. TCA, Cinn, and PI as stabilizing agents prevent agglomeration of silver, resulting in smaller AgNPs and better microbial growth control.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…PI is a stabilizing agent and reservoir for triiodide anions releasing free molecular iodine for biocidal action [32,48]. AgNP is a drug carrier and adsorbs TCA, Cinn, and PI on its large surface [57,60]. TCA, Cinn, and PI as stabilizing agents prevent agglomeration of silver, resulting in smaller AgNPs and better microbial growth control.…”
Section: Introductionmentioning
confidence: 99%
“…A promising development is the combination of PVP with iodine nanoparticles and its incorporation into wound dressing materials to inhibit bacteria and biofilm formation which may reduce the above adverse effects due to minimizing the iodine content [31,48].Nanotechnology offers a wide range of medical applications including biodegradable, plant and polymer-based antimicrobial compounds [51][52][53][54][55][56]. Nanomedicine includes organic and inorganic drug delivery systems, ensuring long shelf life with reduced drug loss and low toxicity [15,57].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Incidence of hospital-acquired infections was directly related to hospitalization time and nosocomial infection by multidrug-resistant pathogens, with Acetinobacter baumanii as the most common strain isolated from the lower respiratory tract [60]. Nanotechnology is delivering promising future perspectives to develop vaccines and solutions against antibiotic resistance [61][62][63][64][65][66]. Jorquera et al reported on nanovaccines against the respiratory syncytial virus [64].…”
Section: Role Of Basic Sciences Against Covid-19 and Antibiotic Resismentioning
confidence: 99%
“…lipids, biopolymers, proteins) is quite common. 3 Low sustainability of delivery carriers production stimulates scientists to think about the possible negative environmental impact that the global production of delivery vehicles may have. 4 In view of the above, the quest for alternatives sources for drug delivery vehicles -minerals, bacteria and waste materialsresulted in the rise of a new wave of drug delivery research.…”
Section: Introductionmentioning
confidence: 99%